Social Protest and Policy Attitudes: The Case of the 2006 Immigrant Rallies. Issue 2 (18th November 2014) - Branton, Regina; Martinez‐Ebers, Valerie; Carey, Tony E.; Matsubayashi, Tetsuya
<x xml:space="preserve">Abstract</x> Do protests sway public opinion? If so, why and how? To address these questions, we examine the impact of the 2006 immigration protests on immigration policy preferences. We use the 2006 Latino National Survey coupled with protest data to examine whether temporal and spatial exposure to the protests are associated with policy preferences. Our findings lend evidence that protest activity influences Latinos' immigration policy preferences. However, the findings suggest the effect of protest on immigration policy preferences is not uniform across the population, but rather contingent on generational status and the intensity of protest activity at the local level.